Four- and six-year-olds use pragmatic competence to guide word learning*. Issue 2 (5th January 2012) - VÁZQUEZ, MARIA D.; DELISLE, SARAH S.; SAYLOR, MEGAN M.
ABSTRACT: The present study investigates whether four- and six-year-old children use pragmatic competence as a criterion for learning from someone else. Specifically, we ask whether children use others' adherence to Gricean maxims to determine whether they will offer valid labels for novel objects. Six-year-olds recognized adherence to the maxims of quality and relation and subsequently trusted the labels provided by a maxim adherer. Four-year-olds displayed this pattern when judging adherence to quality but not relation. A linear regression revealed that children's ability to identify maxim adherers predicted their ability to choose the correct object during word-learning trials. This research demonstrates that children use others' pragmatic history when judging the reliability of the information they offer.